2002
DOI: 10.1002/glia.10054
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological localization of the myelinating cell‐specific receptor LPA1

Abstract: LP(A1) (also termed Edg-2 or VZG-1) is a G-protein-coupled receptor for lysophosphatidic acid and its gene transcripts have been found selectively expressed by mature myelin-producing cells. We have raised in rabbit a polyclonal antibody against a sequence unique to LP(A1) and common to rat, mouse, and human orthologues. In Western blots, LP(A1) immunoreactivity appeared as 44-53 kDa bands in extracts from recombinant RH7777 cells expressing LP(A1), mouse purified oligodendrocytes, or human white matter, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 26 publications
6
22
1
1
Order By: Relevance
“…Astrocytes are the most abundant type of glia and play a signifi cant role in developmental, functional, and pathological processes (116). While basal in vivo astrocytes have undetectable levels of LPA 1 (91,92,117), cultured astrocytes express LPA 1-5 (118) and are responsive to LPA. Such effects include calcium infl ux, phosphorylation of ERK, morphological changes, and stabilization of stress fi bers (119)(120)(121).…”
Section: Lpa Receptorsmentioning
confidence: 99%
“…Astrocytes are the most abundant type of glia and play a signifi cant role in developmental, functional, and pathological processes (116). While basal in vivo astrocytes have undetectable levels of LPA 1 (91,92,117), cultured astrocytes express LPA 1-5 (118) and are responsive to LPA. Such effects include calcium infl ux, phosphorylation of ERK, morphological changes, and stabilization of stress fi bers (119)(120)(121).…”
Section: Lpa Receptorsmentioning
confidence: 99%
“…Edg2/LPA1 and Edg8/S1P5 mRNA are predominantly expressed in the CNS white matter (Allard et al, 1998;Im et al, 2001). At the cellular level, Edg2/ LPA1 has been shown to be expressed on mature oligodendrocytes (Allard et al, 1998;Cervera et al, 2002;Stankoff et al, 2002b), whereas its expression on immature oligodendrocytes remains controversial (Moller et al, 1999;Dawson et al, 2003). Immunohistochemical analysis has suggested that Edg8/S1P5 is expressed in NG2-positive OPCs but not in mature oligodendrocytes (Terai et al, 2003), whereas expression of Edg8/S1P5 transcripts has been detected by reverse transcription (RT)-PCR in differentiated rat oligodendrocytes in culture (Yu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and reproducible data can be obtained, provided a standardized system of brain collection, dissection, storage and case matching is employed in conjunction with the consideration of key ante-and post-mortem factors. Techniques in use in our and other laboratories range from quantitative competitive RT-PCR (Cummings et al 2001;Becker et al 2002;Guan et al 2002;Pandey et al 2002), western blotting (Lewohl et al 2001;Mori et al 2002), cDNA microarray (Whitney et al 1999;Lockhart and Barlow 2001;Goldstine et al 2002;Mayfield et al 2002;Tanwar et al 2002), and proteomic assays of unfixed tissue (Cheon et al 2001;Davidsson et al 2001;Husi and Grant 2001;Pasinetti 2001), through to RT-in situ hybridization histochemistry (Schindler et al 1995;Wakeman et al 1997;Hawkins and Dodd 2000;Goldstine et al 2002) and immunohistochemistry on fixed sections (Sparks et al 1998;Cerf and Raidoo 2000;Cervera et al 2002).…”
mentioning
confidence: 99%